Buddhism in the Blockchain Age: An Ethical Analysis of Cryptocurrency - Billy Wheeler (Journal of International Buddhist Studies, 2025)
Like all religious traditions, Buddhism must continually respond to emerging technologies while remaining grounded in its ethical and philosophical foundations. One such technology is cryptocurrency—a decentralized, blockchain-based financial innovation that has reshaped economic life by reducing reliance on traditional banking systems, enhancing user privacy, and offering a hedge against inflation and state-based monetary control. Its adoption has grown rapidly, including among Buddhist communities, where it is used in a variety of ways: as a medium of exchange, as an investment vehicle, and as a means of generating income through mining. For many practitioners, cryptocurrency represents a new and complex challenge in aligning financial management with Buddhist ethical values. For example, critics point to its environmental footprint, its association with illicit trade and financial crime, and its speculative nature, which some argue parallels gambling—an activity explicitly discouraged in Buddhist precepts. This article examines the ethics of cryptocurrency from multiple Buddhist perspectives, drawing on canonical sources such as the Pāli Nikāyas, monastic codes (Vinaya), and recent interpretations by contemporary Buddhist teachers and scholars. It also engages with relevant secular critiques to contextualize Buddhist concerns. The article concludes by proposing a normative framework to assist both lay practitioners and members of the monastic sangha in evaluating the ethical permissibility of engaging with cryptocurrency, guided by key principles such as non-harming, right livelihood, and mindful consumption.